2019
DOI: 10.11648/j.sjedu.20190704.11
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Dyslexia: Definition, Characteristics, Assessment, Identification, and Intervention

Abstract: Background: Dyslexia is a developmental brain-based type of learning disability that affects a person's ability to read and spell words. Best estimates place 5 percent to 10 percent of the population with the condition, but the incidence of dyslexia is challenging to pinpoint, as the definition of dyslexia varies throughout research. Objective: The purpose of this article is to provide an overview of dyslexia, its characteristics, assessment and identification, and intervention techniques for the condition. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
(44 reference statements)
1
21
0
1
Order By: Relevance
“…In line with our expectations, audio-support affected the time students spent on the written text on most tasks: it increased reading time in students with and without dyslexia in open-ended and statement assignments. Even though students with dyslexia had higher reading times, as expected, see, e.g., Roitsch and Watson ( 2019 ), audio-support affected both groups equally. This is in line with Knoop-van Campen and colleagues ( 2020 ) who also showed that audio-support in learning tasks increased study time in university students with and without dyslexia, but contrary to similar research in primary school children who became faster with audio-support (Knoop-van Campen, et al, 2019 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In line with our expectations, audio-support affected the time students spent on the written text on most tasks: it increased reading time in students with and without dyslexia in open-ended and statement assignments. Even though students with dyslexia had higher reading times, as expected, see, e.g., Roitsch and Watson ( 2019 ), audio-support affected both groups equally. This is in line with Knoop-van Campen and colleagues ( 2020 ) who also showed that audio-support in learning tasks increased study time in university students with and without dyslexia, but contrary to similar research in primary school children who became faster with audio-support (Knoop-van Campen, et al, 2019 ).…”
Section: Discussionsupporting
confidence: 75%
“…Decoding remains effortful, and reading speed remains slow. In line with the Simple view of Reading (Hoover & Gough, 1990), these decoding problems may have a severe impact on students' reading comprehension (Lyon et al, 2003;Roitsch & Watson, 2019). As ineffective decoding is considered to have a negative effect on the available resources for understanding the text (Smythe, 2005;Wolf & Katzir-Cohen, 2001), reading comprehension can be compromised, because the student can only process a certain amount of information at once.…”
Section: Reading Comprehension In Students With Dyslexiamentioning
confidence: 99%
“…It is a disorder in one or more of the basic psychological processes involved in understanding or using language, speech or writing and can manifest itself in the imperfect ability of a person to hear, think, speak, read, write or carry out mathematical calculations. The most persistent problem, however, seems to be diction (Roitsch and Watson 2019). More specifically, when a student with dyslexia begins to learn how to read, they have difficulty with the level of voice or sound, which adversely affects spelling and reading.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, when a student with dyslexia begins to learn how to read, they have difficulty with the level of voice or sound, which adversely affects spelling and reading. Secondary consequences may include reading comprehension problems and reduced reading experience, which may impede the development of vocabulary and background knowledge (Roitsch and Watson 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexia affects an estimated 5%–10% of the U.S. population and varies significantly in its severity. Its symptoms also vary depending on age [ 11 ].…”
Section: Introductionmentioning
confidence: 99%